2016
DOI: 10.1002/pola.28263
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the halogen and organometallic function in a KCTP (Co)polymerization

Abstract: The effect of changing the halogen and the organometallic function in a Kumada Catalyst Transfer Polycondensation (KCTP) of poly(3‐alkylthiophene)s (P3AT) is investigated. On the one hand, the bromine substituent is replaced with chlorine in the commonly used 2‐bromo‐5‐chloromagnesio‐3‐hexylthiophene. The effect on the homopolymerization is clear, since the stickiness decreases remarkably, but copolymerizations are hardly affected when a chlorinated monomer is used. Second, the option of changing the organomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…The combination of the Grignard reagent with the organozinc monomer was previously examined by our research group, and showed not only the formation of 1, but also equal amounts of 2. 16 In this study, a similar observation was made when the stannylated compound was combined with the Grignard reagent, although slightly longer mixing (10 minutes) at room temperature was required. Nevertheless, it clearly indicates that exchange occurs between the monomers.…”
Section: Compatibility Of the Grignard Monomersupporting
confidence: 65%
See 2 more Smart Citations
“…The combination of the Grignard reagent with the organozinc monomer was previously examined by our research group, and showed not only the formation of 1, but also equal amounts of 2. 16 In this study, a similar observation was made when the stannylated compound was combined with the Grignard reagent, although slightly longer mixing (10 minutes) at room temperature was required. Nevertheless, it clearly indicates that exchange occurs between the monomers.…”
Section: Compatibility Of the Grignard Monomersupporting
confidence: 65%
“…These are chosen because (1) the synthesis of poly(thiophene) using different organometallic functions and catalysts is widely investigated and ( 2 S1, ESI). 16 In addition, they are known to randomly copolymerize when bearing the same organometallic function, so the effect of the different organometallic functions is easily detected. 16,17 The organometallic functions used in this study are (1) Grignard, (2) organozinc, (3) organoboron, (4) organotin, and (5) organogold (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the discovery of the quasi-living synthesis of polythiophenes, considerable effort has been devoted to understanding the underlying reaction mechanisms and expanding the scope of applicable monomers. Nickel( ii )diphosphine catalysts, such as 1,2-bis-(diphenylphosphino)propane nickel( ii ) chloride (Ni(dppp)Cl 2 ) and 1,2-bis-(diphenylphosphino)ethane nickel( ii ) chloride (Ni(dppe)Cl 2 ), are most frequently used for the controlled synthesis of electron-rich conjugated polymers, and their polymerizations are often used as model systems for studying the mechanism of KCTP 7…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the mechanism of the catalyst transfer condensative polymerization (CTCP) of especially thiophene monomers has thoroughly been investigated. 1 This includes the influence of the ligand of the catalyst [2][3][4] , the halogen on the monomer 5,6 , the use of different precursor monomers and synthetic methods for obtaining the monomers [6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%